Natural and bioinspired silk spinning - Davies, G (2014)
This thesis describes an investigation into silk spinning, with the objective of producing high performance silk fibres in the laboratory using a novel spinning device based upon observations on natural spinning glands and processes. After an in-depth literature review the work is reported in two sections: natural and artificial spinning. The literature provides fragmented data on different aspects of natural silk production, and artificial spinning has not yet reproduced fibres with the properties of native silk fibres, despite unfounded claims of biomimetic spinning. The first half of the thesis looks at natural silk spinning. The work started with a general study of the morphology of spider and silkworm spinning ducts: First, how the silk fibre develops as the dope flows through the gland; and second the relationship between silk fibre properties and both gland morphology and spinning speed. More detailed studies using histochemical and spectroscopic investigations showed that the silk ducts of the spider Nephila edulis and the silkworm Bombyx mori both contain β-chitin, despite an evolutionarily distant common ancestor. Finally, observations showed that the duct of N. edulis consists of alternating nanoporous discs, and FEA modelling indicated that the duct is optimised for mechanical integrity and permeability. The second half of the thesis describes the development of a spinning device that uses natural silk dope mainly taken from B. mori as feedstock. It begins with a description of the gradual development of the engineering aspects of the spinning device, to meet challenges raised during the spinning investigation. The development of a centrifugal capillary rheometer, for practical quantitative insights into rheological processes is then presented. Finally the spinning investigation is reported: first, the screening of spinning in glass capillaries based upon natural gland dimensions and flow rates, which have been shown to induce fibrillation in silk dope in a rheometer, and also included initiation of instability through heat applied along the capillary; second, the final spinning evaluation, using lessons learned from all the screening trials throughout the project, but also including a key development of a hydrophobic coating on the capillary tip to inhibit droplet formation and massively increase the process stability and ease of fibre production. The main conclusions from this work are that good silk fibre cannot be spun by flow shear stress alone; and, that heat instability induces indiscriminate gelation of the silk, whose disordered molecular structure gives poor silk fibre properties. The body of work behind these conclusions provides fundamental background information and new insights that will contribute to the next stages of development of artificial silk spinning, from obtaining a better understanding of the biology of natural spinning glands to the engineering difficulties of implementing the bioinspired principles.